Biogenic composition of calcium carbonate over the past 140,000 years: clues from a marine core in the Santos Basin (Ocean and Coastal Research, 2024)
This study aimed to investigate the biogenic composition of calcium carbonate (CaCO 3) in pelagic sediments in the Santos Basin over the past 140,000 years. The content and composition of CaCO 3 in different sediment fractions were evaluated, including the bulk sample, coarse fraction (foraminifera), medium fraction (juvenile foraminifera and fragments), and fine fraction (nannofossils), to determine the contribution of each fraction to the carbonated sediment composition. We found that variations in CaCO 3 levels were closely linked to glacial and interglacial periods, with higher values during interglacial periods and lower values during glacial periods. The main factor controlling the variation in CaCO 3 was dissolution, which was mainly linked to the influx of more corrosive southern water masses. Fluctuations in CaCO 3 levels were influenced by variations in productivity and dilution caused by terrigenous sediments. Nevertheless, it is noteworthy that both processes held a relatively minor impact compared to dissolution. Productivity primarily contributed to increased dissolution rates. During periods of low sea levels, dilution by terrigenous sediments became significant (similarly, the influence of the La Plata River plume was notable). However, due to the limited presence of riverine supply in the study area, which contributes directly to major dilution influences, fluctuations in terrigenous materials were considered of lesser magnitude than those caused by dissolution. The nannofossils were found to be the largest contributor to the total CaCO 3 composition, as they were the fraction least affected by the dissolution process. Overall, our results provide insights into the factors influencing CaCO 3 accumulation in marine sediments and can be used as a tool to determine changes between climatic cycles over time.